2019
DOI: 10.1186/s12966-019-0793-6
|View full text |Cite
|
Sign up to set email alerts
|

Results from a natural experiment: initial neighbourhood investments do not change objectively-assessed physical activity, psychological distress or perceptions of the neighbourhood

Abstract: Background: Few studies have assessed objectively measured physical activity (PA), active transportation, psychological distress and neighborhood perceptions among residents of a neighborhood before and after substantial improvements in its physical environment. Also, most research-to-date has employed study designs subject to neighborhood selection, which may introduce bias in reported findings. We built upon a previously enrolled cohort of households from two low-income predominantly African American Pittsbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
(83 reference statements)
1
13
1
Order By: Relevance
“…Those studies reported associations between subjective assessments or macro-scale data on distance to a nearby resource, whereas our study used micro-scale audits of environmental features. Dubowitz et al (2019) found no significant difference in BMI between residents in the Hill and Homewood neighborhoods, though unlike our study that analysis did not include micro-scale data on the environment (Dubowitz et al, 2019).…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Those studies reported associations between subjective assessments or macro-scale data on distance to a nearby resource, whereas our study used micro-scale audits of environmental features. Dubowitz et al (2019) found no significant difference in BMI between residents in the Hill and Homewood neighborhoods, though unlike our study that analysis did not include micro-scale data on the environment (Dubowitz et al, 2019).…”
Section: Discussioncontrasting
confidence: 72%
“…Several recent natural experiments have examined how changes to the built environment influence health focusing specifically on African American adults and low-income racial and ethnic minorities. A longitudinal assessment of the built environment, physical activity, BMI and neighborhood satisfaction was conducted in two low-income, African American communities in Pittsburgh, PA, USA, which are the primary focus of this study (Dubowitz et al, 2019). A natural experimental design was used to track participants' activity, BMI, and neighborhood satisfaction before and after one of the neighborhoods received investments that improved the built environment, such as new residential buildings, sidewalks, and street crossings.…”
Section: Built Environment and Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, DID has been used to estimate the association between neighborhood condition and weight changes while accounting for potential self-selection due to movers and non-movers [ 54 ]. The method has also been used to estimate the effect of neighborhood investment on physical activity and body mass index adjusting for general changes over time [ 55 ]. In addition, a DID approach has been used to examine self-selection [ 56 ], by estimating how baseline health may relate to changes in NE characteristics after the baseline time period.…”
Section: Methods To Address Reverse Causality and Self-selectionmentioning
confidence: 99%